Pembinaan negara bangsa Malaysia : peranan pendidikan sejarah dan dasar pendidikan kebangsaan - Mohamad Rodzi Abd Razak, (Penerbit UKM, 2009)
This article aims to examine the importance of history and history subject as a tool for strengthening the nation-building process and attaining the objectives of the national education policy. After 52 years of independence, the question of nation-building still continues unabeted. Certain groups and individuals continue to question many issues that were deemed sensitive in this multi-ethnic society, including the special rights, the Malay supremacy, as well as the roles and contributions of particular ethnic groups to the country. At the same time, there are also disputes over the history syllabus in schools. All these problems occurred as a result of the country’s failure in cultivating nationalism and patriotism among the people. The question is: why has this continued to happen? The education sector as an agent of change has seemed to be incapable of promoting nation-building. This article argues that such an enduring problem is attributable to at least three major factors, namely a narrow syllabus band, a flawed teaching and learning method, as well as an over-emphasis on examination.